Novel technique for electric stress reduction across ceramic disc insulators used in UHV AC and DC transmission systems. (1st January 2017) - Subba Reddy, B.; Verma, Alok Ranjan
Highlights: A novel technique is proposed to improve electric stress in ceramic insulator string. Stress control electrodes are designed to reduce partial arcs flashovers. Potential and surface electric stress estimated for faulty discs in string. Results presented for full strings operating under normal, polluted conditions. Abstract: In the recent years there has been a considerable increase in the demand for electrical power requirement across the globe. The transmission voltage levels have increased to 765 kV ac and ±800 kV dc. Further HVDC transmission is becoming increasingly viable as it is more economical for long distance transmission and can carry large amount of power compared to same voltage levels as of HVAC. One of the major problems encountered by the utilities is the failure of overhead transmission insulators due to the pollution/contaminated conditions. The insulator failure rate is observed to be higher in DC as compared to the AC transmission systems. The present work is intended to focus on a practically new technique which enhances the surface potential and electric field strength for the existing ceramic disc insulators used for both HVAC and DC transmission. With this technique, substantial reduction in the discharge activity is obtained near the high voltage end of the disc insulator. It is known that faulty discs may alter the field conditions of the remaining discs in a sting, to study the redistribution of field and potential an attempt is made to compute the surface potential, electric field across the ceramic disc insulator string by using developed Surface Charge Simulation Method (SCSM) code. Simulation study is conducted for 1200 kV ac and ±800 kV dc systems under normal, with string containing faulty discs at arbitrary locations and for different contaminated conditions. Interesting results are obtained from the study; it is believed the results presented will be useful to the utility and design engineers.